KONSEP MAQASHID SYARIAH PADA UMKM DALAM UPAYA MENDUKUNG AKSELERASI PANGSA EKONOMI SYARI’AH JAWA TIMUR - M. Zikwan (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2021)
The existence of UMKM is very urgent for the community because it can provide solutions for workers who have not been accommodated. This is because UMKM are businesses that come from someone's creative thinking and do not have high criteria in absorbing labor. The reality is that UMKM have been able to survive in the welfare of people's lives both under normal conditions or in conditions of economic crisis, in fact in the 1997 economic crisis UMKM were able to provide solutions and continue to survive until economic conditions returned to stable. Along with the rapid development of UMKM, it often causes local conflicts and so on, to prevent this it is necessary to take preventive actions taken by the government against UMKM based on sharia principles. To realize UMKM that are in accordance with sharia principles, it is necessary to involve the government to make regulations related to the technical and implementation of UMKM. The standards for sharia UMKM are UMKM that have implemented sharia principles. There are five aspects that must be guarded by humans, namely religion (حفظ الين) soul (حفظ النفس) intellect (حفظ العقل) offspring (حفظ النسل) property (حفظ المال).